CG9925 and CG9684 are homologues of the TDRD1 piRNA protein family and occupy different subcellular compartments in the Drosophila germline - Macedo, André Lopes Martins (2014)
Tese de mestrado em Bioquímica, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2013